2021
DOI: 10.1007/s40122-021-00256-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesic Efficacy of Erector Spinae Plane Block in Patients Undergoing Lumbar Spinal Surgery: A Systematic Review and Meta-Analysis

Abstract: Lumbar spine surgery is one of the most widespread types of surgery for treating back and leg pain. However, the postoperative period always presents with severe pain due to the removal of skin, subcutaneous tissues, bones, and ligaments. Patients usually require high doses of opioids to relieve pain during the initial three days after operation, as well as experience drugrelated complications and prolonged length of stay in hospital. We found that Erector spinae plane block significantly reduced postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…ESPB is a relatively easy regional block to operate, and previous larger sample size studies demonstrated that ESPB is safe [ 28 , 29 ]. There are only a few case reports of operation-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…ESPB is a relatively easy regional block to operate, and previous larger sample size studies demonstrated that ESPB is safe [ 28 , 29 ]. There are only a few case reports of operation-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most significant advantages of regional anesthesia is that the area and duration of analgesia can be modified by changing the anesthetic volume or using a supplemental catheter. ESPB, a novel technique, may be appropriate for managing perioperative pain in patients undergoing lumbar spine surgery from the perspective of anatomical approaching [5]. Further studies are required to confirm the effectiveness and safety of ESPB.…”
mentioning
confidence: 99%
“…Many studies have shown that postoperative opioid consumption can be reduced by ESP block [ 11 ]. It is recommended to use local anesthetic techniques to reduce perioperative opioid consumption in ERAS (enhanced recovery after surgery) protocols.…”
Section: Discussionmentioning
confidence: 99%